2018
DOI: 10.1007/s12298-018-0555-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, biochemical and morphoagronomic characterization of drought-tolerant and drought-sensitive bean genotypes under water stress

Abstract: Water deficit is one of the main factors that reduce grain yield. A better understanding of the mechanisms related to this abiotic stress is a key aspect to design and act upon drought tolerance improvement in crop plants. Therefore, the major objective of this study was to investigate four common bean genotypes for drought tolerance and to establish their tolerance mechanisms. The experiment was carried out in a greenhouse, using the completely randomized design in a factorial arrangement (2 9 4), composed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The significant effect of the water deficit x genotype interaction on morphoagronomic traits (NN, PH, NP, and GY) indicated a variation in the performance of the genotypes under control and water‐deficit conditions. This finding is in agreement with the results of Androcioli et al (2020), Mazengo et al (2019), Arruda et al (2018), Porch et al (2009), and Boutraa and Sanders (2001), who also reported a variation in the responses of common bean genotypes to different water regimes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The significant effect of the water deficit x genotype interaction on morphoagronomic traits (NN, PH, NP, and GY) indicated a variation in the performance of the genotypes under control and water‐deficit conditions. This finding is in agreement with the results of Androcioli et al (2020), Mazengo et al (2019), Arruda et al (2018), Porch et al (2009), and Boutraa and Sanders (2001), who also reported a variation in the responses of common bean genotypes to different water regimes.…”
Section: Discussionsupporting
confidence: 93%
“…Plant species behave differently in water deficit conditions. Common beans are a crop sensitive to drought stress (Arruda et al, 2018; Singh, 1995) because their plants have a C3 metabolism, characterized by their limited photosynthetic ability and low efficiency in water absorption (Fancelli et al, 2015). The magnitude of the damages caused by drought stress depends on the severity, the crop development stage and genotypes' tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Common bean (Phaseolus vulgaris L.) is a drought-sensitive vegetable crop, and water stress may have a detrimental effect on crop yield [21] and the chemical composition of pods and seeds [22,23]. So far, there is limited literature regarding the use of biostimulants on common bean plants, whereas various studies have tested the effects of biostimulants on other legume species, especially under drought stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…BAT 477 is a common breeding line with indeterminate prostrate growth habit type III ( Singh, 1982 ). This genotype was reported to be tolerant to drought stress ( Arruda et al., 2018 ), and it has been widely used as a source of resistance to ASB. However, low to high levels of resistance were reported in previous studies in the greenhouse and field ( Mayek-Pérez et al., 2009 ; Viteri and Linares, 2017 ; Viteri and Linares, 2022a ; Viteri et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%